2006
DOI: 10.1080/13676260500523580
|View full text |Cite
|
Sign up to set email alerts
|

Nightclubbing and the Search for Identity: Making the Transition from Childhood to Adulthood in an Urban Milieu

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…La utilización excesiva de las drogas funciona como parte importante de la resistencia a lo establecido y como abandono individual [21][22][23][24][25][26][27] . Por otro lado, estos trabajos señalan también que el clubbing, relacionado con las raves, permite la propia expresión [27][28][29] y la conformidad con las normas juveniles 30 , actuando como una parte importante tanto en la formación identitaria personal como social de los jóvenes, así como dentro de la edad adulta 34 .…”
Section: Research On Substance Use and Clubbingunclassified
See 1 more Smart Citation
“…La utilización excesiva de las drogas funciona como parte importante de la resistencia a lo establecido y como abandono individual [21][22][23][24][25][26][27] . Por otro lado, estos trabajos señalan también que el clubbing, relacionado con las raves, permite la propia expresión [27][28][29] y la conformidad con las normas juveniles 30 , actuando como una parte importante tanto en la formación identitaria personal como social de los jóvenes, así como dentro de la edad adulta 34 .…”
Section: Research On Substance Use and Clubbingunclassified
“…[21][22][23][24][25][26][27] On the other hand, such work also notes that rave-related clubbing allows for self-expression [27][28][29] and conformity to youth norms 30 , acting as an important part of both personal and social identity formation in youth [31][32][33] , as well as into adulthood. 34 Given these two subcultural traditions, we would expect to find today's clubbers motivated toward and motivated toward and motivated involved in music scenes because of deviant and druginvolved in music scenes because of deviant and druginvolved related experiences, goals, and activities. Even though both subcultural approaches discussed important social and cultural constructs, they maintain that individuals get involved in clubbing because of their subcultural concerns about drugs and, to a lesser extent, alcohol.…”
Section: Research On Substance Use and Clubbingmentioning
confidence: 99%
“…Other benefits of EDM participation discovered by researchers include an experience of rites of passage (Northcote, 2006), enhanced psychological health and wellbeing (Hunt et al, 2007;Hutson, 1999Hutson, , 2000Lynch & Badger, 2006;Sylvan, 2005;Takahashi & Olaveson, 2003), and feelings of solidarity (Kavanaugh & Anderson, 2008). Researchers revealed that EDM culture fostered a social network where participants developed intimate, supportive friendships (Hunt et al, 2007;Lynch & Badger, 2006;Malbon, 1999;Moore & Miles, 2004;Sylvan, 2005;Takahashi & Olaveson, 2003).…”
Section: International Journal Of Transpersonal Studies 57 Edm Eventsmentioning
confidence: 99%
“…Many researchers (e.g., Hutson, 1999;Kavanaugh & Anderson, 2008;Northcote, 2006;St John, 2012a;Sylvan, 2002;Takahashi, 2004aTakahashi, , 2005Takahashi, , 2017 observed how EDM events mirror a variety of spiritual ceremonies, rituals, and shamanic practices performed in various cultures and indigenous, tribal societies. When viewed through this lens, EDM events can be seen as liminal spaces that induce a psychologically subjective state of being on the threshold of, or between, two existential planes.…”
Section: International Journal Of Transpersonal Studies 57 Edm Eventsmentioning
confidence: 99%
“…Clubbing is a socially constructed and performed activity, as well as a series of fragmented, temporal experiences and emotions (Böse, 2005;Northcote, 2006), with a particularly relevant role in gendered performances (Gelder, 2007;Waitt, Jessop and GormanMurray, 2011;Tan, 2012). Many researchers have considered the different perceptions of fun, amusement, annoyance and fear in the eyes of different audiences (e.g., Hutton, 2006;Boyd, 2010).…”
Section: Introductionmentioning
confidence: 99%